Student engagement with teacher written feedback: Insights from low-proficiency and high-proficiency L2 learners. (October 2022) - Cheng, Xiaolong; Liu, Yan
Abstract: Although studies on teacher written feedback have proliferated in recent years, much remains to be discovered about L2 learners' engagement with this practice. To bridge this gap, the study examined how low-proficiency and high-proficiency students engaged with teacher written feedback affectively, cognitively, and behaviorally in a Chinese EFL context. The study collected data from multiple sources including students' first drafts of their writing, teacher written feedback, revised drafts, students' verbal reports, and semi-structured interviews. The findings revealed that for this important pedagogical practice, students' engagement with teacher written feedback was mediated by their language proficiency and feedback focus. Specifically, while LP and HP students' engagement with local feedback was quite different, they shared similarities in their engagement with global feedback. The study further found a complex and nonlinear relationship across the three perspectives of engagement (i.e., affective/cognitive/behavioral), which was evidenced in the consistencies and inconsistencies of the students' engagement. The important pedagogical implications from this study are discussed.